How Gratitude and Self-Image Congruency Can Affect the Satisfaction, Trust and Affective Commitment? - Wiganda, Siska; Marsasi, Endy Gunanto (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study aims to determine the effect of perceived relationship marketing investments, self-image congruency, and customer gratitude on satisfaction, trust, and affective commitment perceived by-product customers who are associated with local brands. Methodology: This study uses a quantitative approach by distributing questionnaires. Hypothesis testing was carried out using SEM (Structural Equation Model) analysis technique on AMOS 24.0 software. The object used is the brand of consumer goods products. This research was conducted by surveying 305 Y and Z generation customers who have used or are currently using the product.Finding: The results of this study indicate that gratitude has a positive and significant effect on trust and affective commitment, and also has a negative and significant effect on overall satisfaction.Conclusion: This research shows that when the customer has felt the relationship marketing investment that a product or organization has made then from then positive feelings and a greater sense of gratitude will arise for the product or organization. Keywords: Affective Commitment; Customer Gratitude; Perceived Relationship Marketing Investment; Satisfaction; Self-Image Congruence; Trust.